Ð˜ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð°Ð¿Ð¾Ð¿Ñ‚Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð¿Ñ€Ð¾Ñ†ÐµÑÑÐ¾Ð² Ð² ÐºÐ»ÐµÑ‚ÐºÐ°Ñ… Ð¼Ð¾Ð½Ð¾Ñ†Ð¸Ñ‚Ð°Ñ€Ð½Ð¾-Ñ„Ð°Ð³Ð¾Ñ†Ð¸Ñ‚Ð°Ñ€Ð½Ð¾Ð¹ ÑÐ¸ÑÑ‚ÐµÐ¼Ñ‹ Ð¿Ñ€Ð¸ Ñ€Ð°Ð·Ð²Ð¸Ñ‚Ð¸Ð¸ Ð°Ð´ÑŠÑŽÐ²Ð°Ð½Ñ‚Ð½Ð¾Ð³Ð¾ Ð°Ñ€Ñ‚Ñ€Ð¸Ñ‚Ð° Ð´Ð¾ Ð¸ Ð¿Ð¾ÑÐ»Ðµ Ð²Ð²ÐµÐ´ÐµÐ½Ð¸Ñ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ - Goltsev, Anatoliy N.; Yampolskaya, Ekaterina E.; Ostankov, Maksim V.; Bondarovich, Nikolay A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
Rheumatoid arthritis (RA) is one of the most widespread chronic inflammatory diseases of the joints with multifactor etiology. A crucial point in RA is the disorder of proliferation and apoptosis in immunocompetent cells as well as in the cells of monocyte-phagocyte system (MPS). Using the model of adjuvant arthritis (AA) in animals we comparatively assessed the development of apoptotic processes in MPS cells before and after administration of native and cryopreserved fetal liver cells (cFLCs). By means of Western blot analysis we showed the peculiarities of CD-95 cascade proteins expression in MPS cells during development of AA. After administration of cFLCs we found more pronounced proapoptotic effect, which degree depended on the period of theiradministration.Probl Cryobiol Cryomed 2014; 24(3):249-261.